Molecular dynamics simulations of polymer viscoelasticity: effect of the loading conditions and creep behavior - Simões, Ricardo João Ferreira (2006)
Deformation brings out important features of viscoelastic behaviour in polymers. To achieve a better understanding of the underlying phenomena, molecular dynamics simulations have been performed for one- and two-phase polymeric materials created on the computer. An external force was applied to the materials and their response followed as a function of time. The mechanical properties were found to be strongly affected by the loading conditions, particularly the force increase rate. The simulated materials exhibit a realistic response: the behaviour is more rigid and brittle when the force increases at a higher rate. The material is able to partially recover in a viscoelastic manner if the force is removed after deformation. There are both quantitative and qualitative differences between the engineering stress and true stress. The presence of a rigid phase in polymer liquid crystals (PLCs) significantly influences their mechanical properties. Higher liquid crystalline (LC) phase concentrations increase stiffness while they make the polymer more brittle. The viscoelastic phase shift is smaller in PLCs than in one-phase amorphous polymers; the LC-rich islands in the LC-poor matrix make the material more elastic. When a creep force is applied for some time and then removed, the material exhibits partial viscoelastic recovery. The extent of that recovery is dependent on the magnitude of the creep force; a higher applied force results in less recovery. It also depends on the time during which the force was applied; longer times will result in less recovery. These results could be expected confirming the model’s validity. Unexpectedly the deformation mechanisms at higher stress levels were found to be different from those taking place at lower force levels. This reflects on a more localized deformation for higher creep force levels